2010
DOI: 10.3109/10253890903362645
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute restraint stress on nociceptive responses evoked by the injection of formalin into the temporomandibular joint of female rats

Abstract: The temporomandibular joint (TMJ) formalin test was used to evaluate the effects of acute restraint stress on the nociceptive behavioral responses of female rats during proestrus and estrus phases of the estrous cycle. Rats were subjected to one session of restraint stress (15, 30 min or 1 h). They were then either immediately killed to allow the collection of blood for hormonal radioimmunoassay determinations or subjected to TMJ formalin test to evaluate nociception. All stress protocols significantly raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…In this study, we show that both acute and repeated restraint stress resulted in stress‐induced analgesia that was blocked by pretreatment with BU10119 and the combination buprenorphine/naltrexone. Restraint stress‐induced analgesia is blocked by pretreatment with the κ antagonist norBNI in female rats (Botelho et al, ) and in mice exposed to forced swim stress (McLaughlin et al, ). Interestingly, forced swim stress‐induced analgesia has been shown to be absent in prodynorphin −/− mice (McLaughlin et al, ) but is not altered in κ receptor knockout mice (Contet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show that both acute and repeated restraint stress resulted in stress‐induced analgesia that was blocked by pretreatment with BU10119 and the combination buprenorphine/naltrexone. Restraint stress‐induced analgesia is blocked by pretreatment with the κ antagonist norBNI in female rats (Botelho et al, ) and in mice exposed to forced swim stress (McLaughlin et al, ). Interestingly, forced swim stress‐induced analgesia has been shown to be absent in prodynorphin −/− mice (McLaughlin et al, ) but is not altered in κ receptor knockout mice (Contet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although, animals subjected to restraint stress did not show more pronounced bone loss than unstressed animals in groups with induced PD, despite the numbers of inflammatory cells being significantly higher in groups with stress. These differences can be justified by variations in restraint periods, manner of restraint, 34 and sex susceptibility, since females are more prone to stress models than males 35 . It was observed that bone loss in animals undergoing ligature and the stress protocol showed slightly less bone loss than the unstressed groups (although not significantly less), indicating a possible anti‐inflammatory effect of plasma corticosterone levels in stressed animals, reducing bone loss in animals with respect to induction of the disease alone 4 …”
Section: Discussionmentioning
confidence: 99%
“…A major disadvantage of the commonly used 'pedestal over water' and 'inverted flower pot' methods of sleep disruption is the potential for confounding stress responses (Suchecki et al, 1998;Andersen et al, 2009). As both acute and chronic stress can differentially interfere with pain outcome measurements (Bardin et al, 2009;Botelho et al, 2010;Lafrance et al, 2010;Heidari-Oranjaghi et al, 2012;Spezia Adachi et al, 2012), a low-stress model of sleep disruption may be preferable when studying nociceptive thresholds following reduced sleep. In the present study, we found no significant change in plasma corticosterone levels.…”
Section: Figurementioning
confidence: 99%